BEP Analysis & Risk Management In the Decision Making of the Declaration of Bankruptcy - Haryantini, Haryantini; syahnego, syahnego (ADPEBI, 2022)
Break Event Point Analysis and Risk Management Analysis on the decision to close a business temporarily or permanently are presented in this study so that the company and the shareholders in it are able to determine when to take exit actions and declare bankruptcy. The research was conducted at PT CBP which is engaged in the Indonesian electricity industry. This topic is important because the firmness of the bankruptcy statement has the consequence of a number of burdens that must be borne by a legal business entity related to fulfilling obligations according to labor laws and regulations, and fulfilling obligations to return business capital to shareholders. Financial calculations in the field of asset value against debt obligations and financial calculations on operating costs are the comparison factors that determine the threshold for making this bankruptcy decision. This study will present data related to BEP variables, asset value data, debt liability data, and operational data. Furthermore, a number of these facts and data are entered into the risk analysis matrix. By modifying hibernation operational decisions, companies can avoid bankruptcy, namely by doing an exposure type, releasing some of the ownership of existing assets, continuing business with hibernation mode.